Assessment And Intervention of New Learner Anxiety in Junior High School: A Group Case Study - Ayu Rezki Utari (Journal of Social Science, 2024)
This study aims to evaluate the anxiety levels of new students at Junior High School (SMP) and to identify effective interventions to reduce it. A case study was conducted on a group of seventh-grade students at an SMP in Jakarta. The research method used was a quantitative survey with a validated anxiety questionnaire, as well as in-depth interviews to gain a more comprehensive understanding of the factors influencing anxiety. The results showed that high anxiety levels correlate with factors such as adaptation to a new environment, academic pressure, and social relationships. Several interventions implemented included school orientation programs, counseling sessions, and extracurricular activities designed to enhance social skills and self-confidence. These findings are expected to provide guidance for educators and school officials in designing strategies to help new students better adapt to their new school environment.